2005
DOI: 10.1074/jbc.m508168200
|View full text |Cite
|
Sign up to set email alerts
|

Pias1 Interaction and Sumoylation of Metabotropic Glutamate Receptor 8

Abstract: Group III presynaptic metabotropic glutamate receptors (mGluRs) play a central role in regulating presynaptic activity through G-protein effects on ion channels and signal transducing enzymes. Like all Class C G-protein-coupled receptors, mGluR8 has an extended intracellular C-terminal domain (CTD) presumed to allow for modulation of downstream signaling. In a yeast two-hybrid screen of an adult rat brain cDNA library with the CTDs of mGluR8a and 8b (mGluR8-C) as baits, we identified sumo1 and four different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 45 publications
4
58
0
2
Order By: Relevance
“…SUMOylation may thus be a widespread mechanism of channel regulation. The recent description of SUMOylation of the glucose transporters GLUT1 and GLUT4 (30,40), the two-pore potassium leak channel K2P1 (16), and the G protein-coupled receptor mGluR8 (31) further supports the view that SUMOylation is an important regulatory mechanism for integral membrane proteins. In this report we have demonstrated that disruption of Kv1.5 SUMO modification has a significant effect on the biophysical properties of the channel.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…SUMOylation may thus be a widespread mechanism of channel regulation. The recent description of SUMOylation of the glucose transporters GLUT1 and GLUT4 (30,40), the two-pore potassium leak channel K2P1 (16), and the G protein-coupled receptor mGluR8 (31) further supports the view that SUMOylation is an important regulatory mechanism for integral membrane proteins. In this report we have demonstrated that disruption of Kv1.5 SUMO modification has a significant effect on the biophysical properties of the channel.…”
Section: Discussionmentioning
confidence: 81%
“…To date, SUMOylation has been most extensively studied in the context of nuclear proteins, and, in the case of sequence-specific transcription factors, SUMOylation exerts a direct and context-dependent inhibitory role (27,28). SUMOylation, however, is not restricted to this compartment because the SUMO conjugation machinery is found throughout the cell and multiple proteins not associated with the nuclear compartment, such as the plasma membrane K ϩ channel K2P1 (16), are targets for SUMO modification (30)(31)(32).…”
mentioning
confidence: 99%
“…We attribute this to interaction with mGluR7a residues located N-terminally to the -LVI motif that contribute to PICK1 binding, as described for other PDZ-binding motifs (Hung and Sheng, 2002). Alternatively, PICK1 might bind indirectly to mGluR7a after sumoylation (Tang et al, 2005); this protein modification may occur N-terminally to the -LVI site and mediate interactions with proteins harboring Sumo-binding motifs, as present in PICK1 (Scheschonka et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are two other reports of sumoylation of membrane-bound proteins. Tang et al (50) reported that metabotropic glutamate receptor 8a (mGluR8a) can be sumoylated, although no functional consequence of sumoylation was assigned, whereas Giorgino et al (51) reported that the glucose transporters GLUT1 and GLUT4 are sumoylated in insulin-sensitive cells, resulting in differential regulation of protein levels. However, these observations were not reported in a disease context.…”
Section: Discussionmentioning
confidence: 99%